2015
DOI: 10.1515/cclm-2014-1128
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood thromboelastometry profiles in women with preeclampsia

Abstract: ROTEM(®) profiles in women with PE were characterized by an increased tissue factor driven clot propagation capability. In addition, higher clot stability due both to the increase in clot firmness and the decrease in blood fibrinolysis was observed. Larger studies are needed to identify the clinical relevance of ROTEM(®) alterations in women with PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…143,145 Patients with PE had a higher plasma TAT complex, F1 þ 2, and D-dimer concentration than normal pregnant women, 126,128,136,140,144,146,147 but other work has shown that the TAT level in PE was not significantly higher compared with normotensive pregnancy. 148 TEG does not demonstrate any changes in PE compared with normotensive pregnancy, 135,137,[149][150][151] except for a maximal amplitude decrease with the platelet count. 135 Clot lysis time in TEG is shortened in PE.…”
Section: Assays Of Hemostasis During Normal Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…143,145 Patients with PE had a higher plasma TAT complex, F1 þ 2, and D-dimer concentration than normal pregnant women, 126,128,136,140,144,146,147 but other work has shown that the TAT level in PE was not significantly higher compared with normotensive pregnancy. 148 TEG does not demonstrate any changes in PE compared with normotensive pregnancy, 135,137,[149][150][151] except for a maximal amplitude decrease with the platelet count. 135 Clot lysis time in TEG is shortened in PE.…”
Section: Assays Of Hemostasis During Normal Pregnancymentioning
confidence: 99%
“…135 Clot lysis time in TEG is shortened in PE. 149,150 Only in women with severe PE, "r" and "k" are slightly increased and "α" is decreased. 151 Preliminary data obtained with thrombodynamics assay in Kazan State Medical University (Kazan, Russia) show that women with PE that developed in the third trimester (n ¼ 20) had clot growth rate increased by 20% compared with the group of healthy pregnant women (n ¼ 94) at the similar gestational age.…”
Section: Assays Of Hemostasis During Normal Pregnancymentioning
confidence: 99%
“…b Control * 30 g/ml 300 g/ml 3000 g/ml Adj. b p-value p-value of MCF increase we observed is small, a recent study demonstrated significant differences when comparing the activated INTEM (ellagic acid) and EXTEM (tissue factor) MCF parameters of healthy pregnant vs. preeclamptic women [25]. Based on our in vitro hypercoagulability findings alone, it is unclear if preeclamptic women have additional risk for thromboembolism in the setting of antifibrinolytic therapy.…”
Section: Discussionmentioning
confidence: 62%
“…During normal pregnancy, plasma fibrinogen is increased and fibrinolysis activity is suppressed, ostensibly to promote coagulability of blood (Thornton and Douglas, 2010). There are conflicting data regarding fibrinogen levels in PE, with some studies, including ours, demonstrating increased (Al-ofi et al, 2014, Kawada, 2015, whilst others demonstrate reduced, circulating levels (Spiezia et al, 2015). Moreover, immunofluorescence microscopy has revealed fibrin deposition in the vascular compartments 4 of the placenta, kidney and liver in severe PE (Arias and Mancilla-Jimenez, 1976, Roberts and Post, 2008, Al-ofi et al, 2014 We recently showed that fibrinogen activates monocytes from women with PE (Al-ofi et al, 2014).…”
Section: Introductionmentioning
confidence: 72%